Taxonomic revision of the Amazonian genus Pseudoernestia (Melastomataceae, Marcetieae) - Silva, Diego Nunes Da; Guimarães, Paulo José Fernandes; Michelangeli, Fabián A.; Braga, João Marcelo Alvarenga (Phytotaxa, 2025)
Pseudoernestia (Melastomataceae: Marcetieae) is a genus comprising two species, P. cordifolia and P. glandulosa, with disjunct distributions along the Amazon Rainforest. The genus is characterized by narrow sepals, petals bearing an apical glandular trichome, antesepalous stamens with aristate ventral appendages and calcarate dorsal appendages positioned opposite the ventral ones, a glabrous ovary with three locules, rarely two, and seeds lacking dorsolateral projections. We present a taxonomic review of Pseudoernestia, including a lectotypification for P. cordifolia, the type species of the genus. Based on herbarium data, we confirmed that P. cordifolia occurs in Venezuela and Brazil, typically on rocky outcrops, whereas P. glandulosa is found in French Guiana and Guyana, primarily on lateritic soils. Pseudoernestia cordifolia is categorized as Endangered, while P. glandulosa is assessed as Least Concern. We provide detailed descriptions, photographs of living specimens, scanning electron microscopy images of the seeds, geographic distribution maps, and notes on conservation status, habitat preferences, and phenology.